All-angle total reflection and negative refraction realized with uniaxial hyperbolic materials by manipulating the orientation of the optic axis. (April 2022) - Su, Chengshuai; Fu, Ceji
Highlights: Identified decoupled modes in uniaxial HMs under linearly polarized incidence. Demonstrated all-angle total reflection with uniaxial hyperbolic materials. Demonstrated all-angle negative refraction with uniaxial hyperbolic materials. Proposed novel design of optical fiber and filter with uniaxial hyperbolic materials. Abstract: Uniaxial hyperbolic materials possess some distinctive electromagnetic properties and thus have received extensive investigations. However, unique reflection and refraction phenomena related to uniaxial hyperbolic materials in hyperbolic bands have not been investigated thoroughly. In this paper, we theoretically and numerically studied the reflection and refraction of a natural hyperbolic material calcite with in-plane anisotropy. Our results show that when the optic axis (OA) of the material is parallel or perpendicular to the incidence plane, all-angle total reflection (ATR) can happen in both Types Ⅰ and Ⅱ hyperbolic bands, while all-angle negative refraction (ANR) can appear only in Type Ⅱ hyperbolic band. Based on the findings, we proposed novel design of fibers and filters. Our findings may extend the understanding of reflection and refraction involved with uniaxial hyperbolic materials and offer new theoretical guidance for design of optical devices.